2021
DOI: 10.33448/rsd-v10i5.15468
|View full text |Cite
|
Sign up to set email alerts
|

Application of an active oxygen (blue®m) with free connective graft technique for root coverage – a case report

Abstract: Gingival recession occurs due to the migration of the gingiva in the apical direction, leading to compromising local aesthetics and root hypersensitivity. Connective tissue graft is the gold standard treatment in these cases improving both functional and aesthetics aspects.The purpose of this case is to report root coverage using the free connective tissue graftingtechnique (CTG) associated with topical application of active oxygen oral gel and mouthwash (blue®m). A 27-year-old female sought care with the main… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Regarding the treatment proposed here, presence of active oxygen in wound healing is essential because it promotes increased cellular metabolism, increased collagen synthesis, increased antibacterial activity, promotes and facilitates the release of growth factors, increases angiogenesis and promotes tissue revascularization (Eisenbud, 2012;Stroparo et al, 2021b;2021c) showing better case prognosis, as demonstrated in the rapid healing and disappearance of the painful symptomatology of the lesions in this report.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Regarding the treatment proposed here, presence of active oxygen in wound healing is essential because it promotes increased cellular metabolism, increased collagen synthesis, increased antibacterial activity, promotes and facilitates the release of growth factors, increases angiogenesis and promotes tissue revascularization (Eisenbud, 2012;Stroparo et al, 2021b;2021c) showing better case prognosis, as demonstrated in the rapid healing and disappearance of the painful symptomatology of the lesions in this report.…”
Section: Discussionmentioning
confidence: 84%
“…In this context, it is known that use of oxygen therapy promotes better tissue healing, as it stimulates angiogenesis, promotes revascularization and has an antimicrobial effect, making healing faster and reducing discomfort felt by patients when used in the postoperative period (Eisenbud, 2012;Stroparo et al, 2021bStroparo et al, , 2021c. These are aspects than can be considered potentially relevant for the treatment of lesions resulting from COVID-19.…”
Section: Introductionmentioning
confidence: 99%